A Bladder Wall Angiomyolipoma as a Manifestation of Tuberous Sclerosis: First Case Report. (18th September 2013) - Kalkan, Mehmet; Şahin, Coşkun; Etlik, Ömer; Uçmaklı, Ergun
Abstract : A 21-year-old female patient admitted to the emergency department complaining of left side pain. Hypovolemic shock, which was probably caused by retroperitoneal bleeding from left sided renal angiomyolipoma, was developed. Abdominal computed tomography showed multiple fat containing lesions in different, regions including right bladder wall, lower pole of left kidney, and right kidney. Some lesions compatible with tuberous sclerosis such as angiofibromas, Shagreen patches, myocardial, and brain hamartomas were also detected. Bladder wall mass showing intra- and extravesical extensions was seen at exploration. We removed the tumor completely preserving bladder trigone. Angiomyolipoma located at lower pole of left kidney was also removed. Diagnosis of bladder angiomyolipoma was confirmed by the immunohistochemical examination. Recurrent or residual mass was not detected at the three-months-follow-up. We report the first case of bladder angiomyolipoma confirmed by histopathologically as a tuberous sclerosis.